Elevated Urinary Matrix Metalloproteinase-7 Detects Underlying Renal Allograft Inflammation and Injury. Issue 3 (March 2016) - Ho, Julie; Rush, David N.; Krokhin, Oleg; Antonovici, Mihaela; Gao, Ang; Bestland, Jennifer; Wiebe, Chris; Hiebert, Brett; Rigatto, Claudio; Gibson, Ian W.; Wilkins, John A.; Nickerson, Peter W.
Abstract : Background: The urinary CXC chemokine ligand (CXCL)10 detects renal transplant inflammation noninvasively, but has limited sensitivity and specificity. In this study, we performed urinary proteomic analysis to identify novel biomarkers that may improve the diagnostic performance of urinary CXCL10 for detecting alloimmune inflammation in renal transplant patients. Methods: In preliminary studies, adult renal transplant patients with normal histology (n = 5), interstitial fibrosis and tubular atrophy (n = 6), subclinical (n = 6) and clinical rejection (n = 6), underwent in-depth urine protein compositional analysis with LC-MS/MS, and matrix metalloproteinase-7 (MMP7) were identified as a potential candidate for the diagnosis of renal allograft inflammation. Urine MMP7 performance was then studied in a larger, prospective adult renal transplant population (n = 148 urines from n = 133 patients) with matched surveillance/indication biopsies. The diagnostic performance of urinary MMP7 and CXCL10 in combination was next evaluated using concordance (C-) statistics, net reclassification improvement and integrated discrimination improvement indices, to determine whether it was better than CXCL10 alone. Results: Urinary MMP7:creatinine (Cr) was lower in normal transplants compared to those with inflammation: glomerulonephritis ( P = 0.009), viral nephropathies ( P = 0.002), interstitial fibrosis and tubular atrophy and inflammation ( P = 0.04), borderline ( P = 0.08), subclinical ( P = 0.01) and clinical rejection ( P = 0.0006), and acute tubular necrosis ( P < 0.0001). Urinary MMP7:Cr and CXCL10:Cr significantly distinguished noninflamed from inflamed biopsies (area under the curve, 0.74 and 0.70, respectively). The addition of urinary MMP7:Cr to CXCL10:Cr improved the diagnostic performance for subclinical and clinical inflammation/injury by integrated discrimination improvement ( P = 0.002) and net reclassification improvement ( P = 0.006) analyses. Conclusions: Urinary MMP7:Cr improves the overall diagnostic performance of urinary CXCL10:Cr for distinguishing normal histology from subclinical and clinical inflammation/injury, but not subclinical inflammation alone. Abstract : Proteomic analyses identified that urinary MMP7 is able to detect renal allograft inflammation/injury and outperform serum creatinine to identify subclinical rejection. The combination of urinary MMP7 and CXCL10 improved distinguishing noninflamed from inflamed/injured renal allografts but not the ability to detect subclinical inflammation of urinary CXCL10 alone. Supplemental digital content is available in the text.